Ngadi Wunu Wunungo: Akulturasi Islam dan Budaya Gorontalo dalam Tadarus Al-Quran - Mustaqimah Hikam (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2020)
This paper focuses on the ngadi wunu wunungo tradition as an acculturation of Islam and Gorontalonese culture in the Qur'anic tadarus in Bone Bolango district. This study used the qualitative method by employing the approach of living the Quran, sociology, culture, and da'wah. The research used interviews, observation, and documentation of the ngadi wunu wunungo tradition. The data sources were the ulama, traditional leaders, community leaders, and participants of ngadi wunu wunungo in Bone Bolango. Findings; Empirical data in the field shows Islam's acculturation and Gorontalo culture in the ngadi wunu wunungo tradition. This is evident from its form, which is a combination of tadarus Al-Qur'an interspersed with the praise of Allah SWT, Sholawat Nabi, Gorontalo poetry, which contains advice and is voiced in a tone that screeched high and buzzed. The research empirically shows that the implementation of ngadi wunu wunungo is a da'wah that must be carried out in Dutch colonialism by ulama and traditional leaders, making this cultural acculturation.